C = - 1/2t + 6
The equation usually looks like this
C = k*t + n
If t = 0 than
C = n (from the table we see that C is 6 if t = 0) than
N = 6 too
For t = 2 and c = 5 we have the equation
5 = 2k + 6
2k = -1
K = -1/2
Length = w+3
P = 2L +2W
50 = 2(w+3) + 2w
50 = 2w +6 +2w
50 = 4w +6
50-6 =4w-6
44 = 4w
44/4 = 4w/4
w = 11
l = 11+3
l = 14
50 = 2L+2W
50 = 2(14) + 2(11)
50 = 28 +22
50=50
Answer:
12
Step-by-step explanation:
its not 12 im just trying to make an account
Answer: x = 0
Step-by-step explanation:
1 - 3x = 3x + 1
then add 3x on both sides
1 = 6x + 1
then subtract 1 on both sides
0 = 6x
then divide by 6 on both sides
0 = x
so x = 0
The answer is 5.5 because 66/12= 5.5, hope this helps..